PERANCANGAN ULANG UI/UX WEBSITE BUMDES BATURITI MENGGUNAKAN METODE SUS DAN DESIGN THINKING - Ida Bagus Indra Dewangkara; Made Niken Novianti; Putu Agisna Fransisco Sara; Ni Putu Ana Rainita (P3M STMIK Profesional Makassar, 2023)
Badan Usaha Milik Desa (BUMDes) Baturiti is one of the businesses managed by the Baturiti village government. In this technological era, BUMDes Baturiti has a website used for marketing their products. Surprisingly, the BUMDes Baturiti website has a user interface and user experience (UI/UX) that falls into the